A boundary value problem with an integral condition for a certain fractional differential equation - Bouthina Sabah Hammou; Abdelkader Djerad; Ameur Memou; Chahla Latrous (Mathematical Modelling and Analysis, 2025)
The aim of this work is to prove the existence and the uniqueness of the solution of one dimensional initial boundary value problem for a parabolic equation with a Caputo time fractional differential operator supplemented by periodic nonlocal boundary condition and integral condition. First, an a priori estimate is established for the associated problem. Secondly, the density of the operator range generated by the considered problem is proved by using the functional analysis method.